The Impact of Oral Maternal Colostrum Administration on the Immune System of Premature Babies - Azizah, Adinda Alfi; Octaria, Yessi Crosita (Journal La Medihealtico, 2024)
In children under five years of age, premature complications are now the second leading cause of death. Colostrum has important benefits in promoting the maturity of premature infants' organ functions and preventing infections. Preterm infants are recommended to be given colostrum orally and pharyngeally as early as possible after birth to provide immune protective effects for their bodies. However, the sucking and swallowing functions of preterm infants are often not optimal, partly due to comorbidities, which poses a significant challenge. As a result, the immune system of preterm infants is often low. This literature review aimed to evaluate the effect of oropharyngeal colostrum feeding through subgroup analysis based on complications. Descriptive research was conducted in April-June 2024 using the literature review method with PRISMA guidelines for RCTs. Literature sources were obtained from Pubmed (MEDLINE), Science Direct, Google Scholar, and Cochrane with a publication limit of the last ten years (2014-2023). Of the 1,657 results, 13 articles met the criteria. A total of 1,451 preterm infants were included in the 13 RCT studies. Results showed a lower incidence of late-onset sepsis and Necrotizing Enterocolitis (NEC) in the group that received oropharyngeal colostrum. The administration of oropharyngeal colostrum was shown to have a positive impact on the development and defense of the immune system of preterm infants, reduce health problems such as sepsis and NEC, accelerate the recovery of birth weight, and reduce the incidence of mortality.